Complementary Nursing Interventions to Improve Consciousness in Stroke Patients: A Narrative Review - Dika Ekivalent Setianingrum; Suhartini Ismail; Ridzki Hastanus Sembada (GLOBAL HEALTH SCIENCE GROUP, 2026)
Stroke is a leading cause of mortality and long-term disability, with disorders of consciousness (DoC) being a critical complication affecting 10–40% of acute stroke patients. Early recovery of consciousness is strongly associated with improved prognosis, reduced ICU stay, and better functional outcomes. Complementary nursing interventions, particularly sensory-based strategies, have emerged as low-risk approaches to enhance arousal and awareness in stroke patients. This narrative review aimed to synthesize evidence on complementary nursing interventions—specifically acupressure and multimodal sensory stimulation—to enhance consciousness in stroke patients. A comprehensive search was conducted across PubMed, Scopus, CINAHL, ScienceDirect, and Google Scholar (August–November 2025). From 316 identified records using keywords such as ‘stroke’, ‘consciousness’, ‘sensory stimulation’, and ‘acupressure’, ten eligible studies involving adult stroke patients were selected and synthesized narratively. The synthesis demonstrated that sensory-based interventions significantly improved Glasgow Coma Scale (GCS) scores, often within three days, while remaining safe and feasible for nurse-led implementation. Beyond arousal, these interventions enhanced cognitive function and behavioral responsiveness through mechanisms involving stimulation of the reticular activating system. However, heterogeneity in protocols currently limits standardization. Complementary sensory interventions offer effective, low-risk strategies for holistic neurorehabilitation. This study contributes to science by establishing the clinical value of early, structured, and personalized sensory stimulation and advocating its integration into routine nursing protocols to optimize patient outcomes.